Language, Native People, and Land Management in Alaska - Gallagher, Thomas J. (ARCTIC, 1992)
The native people of Alaska rely on access to land for subsistence resources. As a result of a series of congressional acts, about 88% of Alaska's land is now managed by federal or state agencies. For native people to retain their subsistence use of resources they must affect agency management decisions. Effective participation in the decision process requires clear translation between English and native languages, of which there are 20 in Alaska. Translation to these languages, even those with few speakers, is important because: elders, the primary decision makers in native communities, are most likely to speak the native language; language survival relates directly to cultural survival; and land management agencies have become the latest Western institutions to suppress native language and culture. Translation, however, is difficult due to substantial differences in English and native language vocabularies, particularly in the area of land management. Three solutions are proposed: training of translators and support of "two-way" terminology workshops; development of a unified glossary of agency management terms; and use of traditional (native) place names and terms by agencies. Agencies are encouraged to provide support to implement these solutions.Key words: native people, language, translation, public participation, land management RÉSUMÉ. Les autochtones de l’Alaska comptent sur l’accès au territoire pour trouver leurs ressources de subsistance. Suite à une série de lois adoptées par le Congrès, environ 88 p. cent des terres de l’Alaska sont maintenant gérées par des agences fédérales ou de l’État. Pour que les autochtones conservent l’utilisation de leurs ressources à des fins de subsistance, ils doivent agir sur les decisions de l’agence concernant la gestion. Une participation efficace dans le processus décisionnel exige une traduction précise entre l’anglais et les langues autochtones - qui sont au nombre de 20 en Alaska. La traduction vers ces langues - y compris celles qui ne sont parlées que par ...